Dampak Stres Kerja dan Beban Kerja terhadap Turnover Intention Karyawan PT Sarana Sumatera Barat Ventura - Nurjanah, Rosita; Zusmawati, Zusmawati (Lembaga Yasin AlSys, 2026)
Turnover intention is one of the important issues in human resource management because it can affect employee stability, work effectiveness, and the sustainability of company operations. However, research specifically discussing the effects of work stress and workload on turnover intention among employees of PT Sarana Sumatera Barat Ventura remains limited. This study aims to analyze the effects of work stress and workload on employee turnover intention. This study used a quantitative approach with a survey design, involving 34 employees selected through total sampling. Data were collected using a questionnaire and analyzed using multiple linear regression and the t-test. The results show that work stress has a positive and significant effect on turnover intention, with a significance value of 0.035. Workload also has a positive and significant effect on turnover intention, with a significance value of 0.016. This finding contributes to the development of the human resource management literature, particularly regarding psychological factors and workload that influence employees’ intention to leave the company. The conclusion of this study emphasizes that proper management of work stress and workload is an important factor in reducing employee turnover intention. The practical implications of this study may serve as a basis for company management in formulating strategies for workload management, work stress control, and improving employee stability.